1985
DOI: 10.3168/jds.s0022-0302(85)81244-3
|View full text |Cite
|
Sign up to set email alerts
|

Path Model of Reproductive Disorders and Performance, Milk Fever, Mastitis, Milk Yield, and Culling in Holstein Cows

Abstract: Path analysis was used to model the direct and indirect relationships among age, previous lactation yield or estimated transmitting ability for milk, body weight, days dry, reproductive disorders, milk fever, mastitis, reproductive performance, current milk yield, and culling. Prospective data were from 784 primiparous and 2,066 multiparous Holstein lactations from 33 herds. Heifers that were older, of lighter weight, or who had lower estimated transmitting ability for milk had more problems, less milk, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
109
3
7

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(137 citation statements)
references
References 28 publications
18
109
3
7
Order By: Relevance
“…As it is seen from Table 3 no of the health disorder complexes was protective; this fact being in accordance with most studies analysing associations among diseases (Curtis et al 1983(Curtis et al , 1985Erb et al 1985;Bendixen et al 1988;Gröhn et al 1989Gröhn et al , 1990aGröhn et al , 1990bGröhn et al , 1994Gröhn et al , 1995Oltenacu et al 1990;Correa et al 1990Correa et al , 1993Klerx and Smolders 1997;Heuer et al 1999). Some papers occasionally mention lower incidence of a health disorder in individuals that suffered from and were treated because of a certain previous disease (Dohoo and Martin 1984;Bendixen et al 1987;Calavas et al 1996;Rajala and Gröhn 1998;Loeffler et al 1999).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…As it is seen from Table 3 no of the health disorder complexes was protective; this fact being in accordance with most studies analysing associations among diseases (Curtis et al 1983(Curtis et al , 1985Erb et al 1985;Bendixen et al 1988;Gröhn et al 1989Gröhn et al , 1990aGröhn et al , 1990bGröhn et al , 1994Gröhn et al , 1995Oltenacu et al 1990;Correa et al 1990Correa et al , 1993Klerx and Smolders 1997;Heuer et al 1999). Some papers occasionally mention lower incidence of a health disorder in individuals that suffered from and were treated because of a certain previous disease (Dohoo and Martin 1984;Bendixen et al 1987;Calavas et al 1996;Rajala and Gröhn 1998;Loeffler et al 1999).…”
Section: Resultssupporting
confidence: 67%
“…It was the closest association we found. Close relationship of retained placenta and metritis was observed very often (Dohoo and Martin 1984;Erb et al 1985;Gröhn et al 1990aGröhn et al , 1994Gröhn et al , 1995Calavas et al 1996;Klerx and Smolders 1997;Heuer et al 1999;Loeffler et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Incidence of pyometra was also associated with significant reduction in MY/CI (14.38%) and highly significant increase in CFS (33.08%), SP (39.24%), DP (33.87%) and CI (11.82%) in Murrah buffaloes. Majority of reports (Erb et al 1985;Balasundaram 2008;Khan et al 2009) also showed a significant increase in average SP in cattle and buffaloes affected with metritis. However, some authors (Mukherjee 1989;Pal 2003) failed to observe any significant influence of metritis on SP of dairy animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the intense selection for increasing yield has resulted in a high risk of health problems around the period between calving and lactation peak. Erb et al (1984) -E-mail: rsteri@uniss.it estimated that around 60% of health disorders occur during the first 40 days of lactation.…”
Section: Introductionmentioning
confidence: 99%